Design of Stone Column to Mitigate Soil Liquefaction: Cases Study of Yogyakarta International Airport - Nicholas Hartono; Teuku Faisal Fathani (Journal of the Civil Engineering Forum, 2023)
A low-to-medium cohesionless soil with low fines content was predominantly observed at the surfaces of Yogyakarta International Airport (YIA). The condition exposed subsoil of YIA to Liquefaction in addition to its location on a high seismic zone which has increased the likelihood of massive ground shaking. This means it is necessary to improve soil condition and vibro-replacement using stone column was selected as the appropriate method due to its recent popularity for the enhancement of sandy ground. Stone column has the ability to reduce the Cyclic Stress Ratio (CSR) of liquefiable soil and can be reliably evaluated. Therefore, this study was conducted to evaluate the risk of Liquefaction at YIA by adopting the SPT-based Liquefaction triggering procedure and presuming its manifestation using Liquefaction Severity Index (LSI). It is pertinent to state that the theoretical approach introduced by Priebe was used to design the geometry and center-to-center distance of stone column. The results were presented in the form of maps with a 50 m × 50 m grid size which include the cut and fill, LSI before and after improvement, stone column spacing, as well as stone column depth. It was discovered that the triangular spacing required for stone column ranged from 1.25 m to 2.5 m while the maximum depth was found to be 6 m. Moreover, stone column inclusion efficiently reduced the severity of Liquefaction from medium to very low for the areas studied. However, stone column has several limitations and this means a combination of soil improvement methods needs to be applied to areas with moderate LSI.